Development of Magnetically Soft Amorphous Microwires for Technological Applications - Valentina Zhukova; Paula Corte-Leon; Juan Maria Blanco; Mihail Ipatov; Lorena Gonzalez-Legarreta; Alvaro Gonzalez; Arcady Zhukov (Chemosensors, 2022)
Amorphous magnetic microwires can be suitable for a variety of technological applications due to their excellent magnetic softness and giant magnetoimpedance (GMI) effect. Several approaches for optimization of soft magnetic properties and GMI effect of magnetic microwires covered with an insulating, flexible, and biocompatible glass coating with tunable magnetic properties are overviewed. The high GMI effect and soft magnetic properties, achieved even in as-prepared Co-rich microwires with a vanishing magnetostriction coefficient, can be further improved by appropriate heat treatment (including stress-annealing and Joule heating). Although as-prepared Fe-rich amorphous microwires exhibit low GMI ratio and rectangular hysteresis loops, stress-annealing, Joule heating, and combined stress-annealed followed by conventional furnace annealing can substantially improve the GMI effect (by more than an order of magnitude).